The Translation of Economic Terms in the Book The Psychology of Money - I Gusti Ayu Mahatma Agung; Ni Wayan Suastini; Ni Putu Shintiya Jesi Putri (Pioneer: Journal of Language and Literature, 2022)
Translating economic terms is a challenging task since the translator needs to understand economics and be able to convey the concepts to the target language. In translating economic books for lay readers, the translator also needs to consider the lexical choice so that the target readers can understand the translation easily. This study aims to analyze the translation procedures applied in the translation of economic terms in the book The Psychology of Money written by Morgan Housel and to find out whether the translation is oriented to the source language or the target language. The data in this study were analyzed qualitatively by using the taxonomy of translation procedures by Vinay and Darbelnet. The results showed that there were seven translation procedures applied in the translation of economic terms: borrowing, calque, literal translation, a combination of borrowing and literal translation, transposition, equivalence, and combination of transposition and borrowing. The literal translation is the most dominant translation procedure applied to translate economic terms. Based on the analysis of the translation procedures, it can be concluded that the translation of economic terms in this study is oriented to the source language.